Placental Index, Placental Characteristics, Birth Weight, and Neonatal Outcome in Pregnancies - Simanjuntak, Leo; Simanjuntak, Patrick Anando (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Recent studies have highlighted the clinical importance of placental weight, as predictors of maternal and neonatal morbidity and mortality. The placental index is the ratio between placental weight and fetal weight. Placental index is considered as a placental efficiency indicator. AIM: This study aimed to describe and determine correlation of placental index with pregnancy and neonatal outcome. METHODS: This study used a cross-sectional design using primary data obtained from Mitra Sejati, Herna, and Methodist Sussana-Wesley Hospital in Medan, Indonesia, for all women with singleton term pregnancy from January to August 2020 and 200 pregnancies were included in this study. RESULTS: Mean birthweight was 3197.47 ± 512.26 g. Mean placental weight was 583.85 ± 96.71 g. Mean placental index was 0.18 ± 0.02. There were no significant mean placental index difference in gravida, parity, neonatal gender, and umbilical cord insertion group. There was a significant positive correlation between birth weight and placental weight (r = 0.52) and a significant and progressive placental index decrease in birth weight group. There was no significant correlation between placental index and Apgar score at 1 and 5 min. CONCLUSION: Placental index was not associated to maternal age, maternal BMI, maternal gravida and parity level, neonates gender, umbilical cord insertion, and Apgar score at 1 and 5 min. There was a significant positive moderate correlation between birth weight and placental weight, meaning an increase in birth weight will be followed by increased placental weight.